Pelatihan Keterampilan Menjahit Dengan Mesin di Pondok Pesantren Putri Islahiyyatul Asroriyah Desa Ringinagung Keling Kepung Kediri - Izza Nila Syarifah; Elisya Sudarti; Pipin Indriani; Nur Hikmah Setio Rini (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2022)
One of the most important non-formal Education programs is training. Because, training has a complex strategic value usually applied to groups. To deceive the lack of ability and overcome unemployment. Pondok Pesantren Putri Islahiyyatul Assroriyyah, many students will eventually return to their respective areas, even though they are given lessons in the cottage about religious knowledge. However, when they have other skills in fields other than science, it will definitely make it easier for them to work in society later. This study aims to describe the implementation of the sewing skills of the students at the Pondok Pesantren Putri Islahiyyatul Assroriyyah and to describe the Sewing Training in improving the entrepreneurial readiness of the students